Systematic Literature Review Dan Analisis Bibliometrik Pengaruh Work From Home (WFH) Terhadap Produktivitas Kerja Karyawan - Andika Wulan Febriani; Budi Eko Soetjipto; Madziatul Churiyah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This literature study focuses on work from home and employee productivity. The strategy used is using the SLR as an instrument for searching research data, then bibliometric literature as a data processor which is analyzed by the VOSviewer software. VOSviewer software analysis techniques are used to analyze articles that have been collected through the Scopus database which are taken as researchers' references. The findings of these articles were referenced from 2013 to 2023 with a total of 547 articles, and only 161 articles were analyzed. Then the scientists continued to clarify the description of the results by using the VOSviewer software in examining co-authorship, co-accurance and citation. This literature study, in totality, presents a more accurate bibliographical objective for future researchers according to the themes discussed. Work from home (WFH) is a work process that is flexible and automatic and provides flexibility for employees to work using telecommuting, teleworking and remote work by utilizing modern digital technology tools as a bridge to work. Work from home (WFH) can be done by all men and women, from 25 to 60 years old. Working flexibly in the "New Normal" focuses on employee work productivity in the potential to work from home more towards working in a work life balance (WLB) which aims to balance work responsibilities and balance life time so as to reduce emotional fatigue from work stress, impact on performance satisfaction whose results affect the size of the wage/salary by obtaining work rewards from the company.